Unraveling the effects of google search on volatility of cryptocurrencies - Cai, Zhao; Liu, Fei; Lim, Eric T. K.; Tan, Chee-Wee; Zheng, Zhiqiang (Association for Information Systems, 2018)
Although cryptocurrencies have garnered enormous public attention in recent times, extensive fluctuations in their prices have deterred prospective investors. Due to the absence of a centralized valuation authority, the credibility of cryptocurrencies as a viable investment vehicle remains elusive. Building on attention theory, this study posits that prospective investors of cryptocurrencies are likely to search online for information before deciding whether to make a commitment. We hence investigate the effects of Google search on the return and risk of 268 cryptocurrencies over 181 trading days. Results indicate that the Google Search Volume Index (SVI) of a given cryptocurrency exerts significant and positive impact on its price and turnover.